Response of a Bidirectional EV Charger to Selected Grid Disturbances - Haque, Md Mejbaul; Jones, Laura; Sturmberg, Bjorn C. P. (2021 IEEE Industrial Electronics and Applications Conference (IEACon), 2021)
A bidirectional charger is a four-quadrant converter. It is a vital element that facilitates the energy exchange between electric vehicle (EV) batteries and the electricity grid. As EVs proliferate throughout distribution grids over the coming years, understanding the performance of different EV chargers is important, especially during grid disturbances. In this paper, we demonstrate grid disturbances such as voltage sags and frequency variations using a grid simulator. These grid disturbances are applied to an off-the-shelf EV charger. Experimental results show that the operation of the EV charger is greatly affected by the grid disturbances. In some cases, the charger disconnects from the grid, disrupting grid services delivery.